The assessment and validation of DNA variants detected by massively parallel sequencing using gene panels - Robberts, Sinead (Stellenbosch : Stellenbosch University, 2021)
Robberts, Sinead. 2021. The assessment and validation of DNA variants detected by massively parallel sequencing using gene panels. Unpublished masters thesis. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/658dd3c5-ac91-427b-8c71-33ecef268cef